The Effectiveness of the Cooperative Integrated Reading and Composition Model Assisted by Scratch Media in Improving the Reading Comprehension Ability of Grade V Students - Anggita Okthaviani; Neneng Sri Wulan; Hisny Fajrussalam (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
The background of the research is based on the urgency of improving national literacy scores, where data from PIRLS and PISA consistently show serious challenges to students' ability to understand texts inferentially and evaluatively, demanding innovation of learning methods. The purpose of this study was to evaluate how effective the Cooperative Integrated Reading and Composition (CIRC) model assisted by Scratch media was in improving students' reading and composition skills in grade V compared to the Canva-assisted cooperative learning. A research method with a quasi-experimental design, which used a sample of 60 students, was used in this quantitative study. Once the data is collected through the pretest and posttest, the N-Gain and Independent-Sample t-tests are used. The results showed that, with p = 0.002, there was a significant difference in improvement between the two groups; the experimental class had an average N-Gain of 0.58, and the control class had an average N-Gain of 0.39. These results show that the CIRC Model is very helpful for Scratch in improving students' reading comprehension, especially with the Appreciation indicator. This is an advantage because Scratch is a knowledge construction tool that encourages more complex data processing. However, the Inferential indicator shows the lowest gains. According to this study, the Scratch-assisted CIRC model is a creative approach to improving literacy in elementary schools.